2012
DOI: 10.1093/annonc/mdr461
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of special types of luminal breast cancer

Abstract: The diagnosis of tubular, cribriform and lobular carcinomas carry distinct prognostic implications. The identification of these special types has a significant utility in luminal breast cancer and should be considered in therapeutic algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 47 publications
2
63
1
Order By: Relevance
“…There is still controversy whether the prognosis of ILC differs from non-ILC [5,[27][28][29]. Contrary to other authors, we observed better DDFS and OS for ILC compared to non-ILC [10].…”
Section: Discussioncontrasting
confidence: 96%
“…There is still controversy whether the prognosis of ILC differs from non-ILC [5,[27][28][29]. Contrary to other authors, we observed better DDFS and OS for ILC compared to non-ILC [10].…”
Section: Discussioncontrasting
confidence: 96%
“…The prognostic utility of the cribriform pattern has not been defined for lung adenocarcinoma, although several previous studies have reported correlations between cribriform pattern and prognosis in adenocarcinoma of various organs. 2227 In prostatic adenocarcinoma, the cribriform pattern has been recognized as a higher grade pattern (Gleason score 4) than the acinar pattern, which comprises simple glandular structures (Gleason score 3). 2224 Egashira et al reported that the presence of a cribriform structure was a significant risk factor for lymph node metastasis in invasive colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18, 19 In addition, the cribriform arrangement has been recognized as a pattern of conventional adenocarcinoma in various organs. 2027 To our knowledge, however, the prognostic significance of the cribriform pattern for lung adenocarcinoma has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been dedicated in the past to identification of special types of breast cancer, that is, those displaying a distinct morphology might exhibit a distinct prognostic and predictive profile compared with invasive ductal carcinomas of no special type or not otherwise specified. 21 Within luminal A breast cancer, several special types display an extremely good prognosis, often approaching or equaling that of the general population. In particular, pure tubular and cribriform carcinomas represent a rare histologic type, correlated with a favorable prognosis.…”
Section: Tailored Treatments Of Luminal a Diseasementioning
confidence: 99%